Adversarial Executive-Legislative Relations on Governance in Nigeria: Insights from Buhariâ€™s Presidency (2015-2019) - Garuba, Rasheed Obasekore; Salawu, Ibrahim O. (NIU Journal of Humanities; Vol. 5 Núm. 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The impasse that characterized the executive-legislature relationship under President Buhariâ€™s administration has become a major concern to Nigerians. This has slowed the processes of governance in Nigeria since 2015 following the inauguration of Dr. Bukola Saraki and Rt. Hon. Yakubu Dogara led National Assembly against the interests of the presidency and the ruling party, All Progressive Congress (APC). The forces in the APC and the presidency had severally moved to indict and remove Saraki from office as the President of Nigerian upper legislative arm using the Code of Conduct Tribunal (CCT) to no avail. This development has culminated in a frosty relationship between the executive and the legislature. Thus, it has become difficult for the APC-controlled executive to reach out to reason with the leadership of the National Assembly on issues of common concern. Relying on secondary data and institutional conflicts theory, the paper argued that to promote good governance and democratic sustainability in Nigeria, the nationâ€™s political actors need to wean themselves off the persistent culture of impunity and flagrant disregard to the rule of law which can be considered a major factor that triggers executive-legislative conflicts in the Buhariâ€™s first term in office as President of the Federal Republic of Nigeria. Keywords:  Adversarial, Executive-Legislative, Relations, Governance, Buhariâ€™s Presidency